ANALISIS PENGEMBANGAN SUMBERDAYA MANUSIA DALAM PENINGKATAN KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN PROVINSI LAMPUNG - Malik Malik; Agustuti Handayani; Sepriadi Sepriadi (e-JKPP, 2022)
The problems in this study are (1) How is the development of human resources in improving employee performance at the Lampung Provincial Personnel Agency? (2) What aspects are the supporters and obstacles in the development of human resources in improving employee performance at the Lampung Provincial Personnel Board? The method used in this research is a descriptive qualitative research method. The use of this method is to describe the development of human resources in improving employee performance at the Lampung Provincial Personnel Agency, to examine qualitatively, The results showed that the development of human resources in improving employee performance at the Lampung Provincial Personnel Board, through) education, there were still employees with high school education (SMA), training had been carried out but not all employees participated regularly Skills, in general, employees have good work skills, although not optimal. While the inhibiting aspects are (1) existing human resources, each of which has an employee who has a high school education background, (2) lack of various supporting facilities in completing work, and frequent lights out, so that it can interfere with the smooth completion of work. (3) The relative absence of educational assistance to employees who continue their education.